2009
DOI: 10.1016/j.injury.2009.06.172
|View full text |Cite
|
Sign up to set email alerts
|

Payment by results (PbR) in orthopaedic trauma: Where are we losing?

Abstract: external fixator or plating anteriorly. 17 patients (group 2) exhibited minimal displacement less than 5 mm and were not stabilised. Rotational instability >2 cm was characterised by complete fracture of the sacrum posteriorly. Stabilisation of the pelvic ring in group I was associated with a significant reduction of the VAS within 72 h from surgery, early ambulation and discharge from the hospital. Conclusion: This study supports the view that not all LCI fracture patterns are mechanically stable. Examination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The use of a template for clinical documentation can also serve as a means for improving resident instruction in coding. Other studies have shown that coding errors and omissions in patients resulted in cumulative loss of revenue of £46,750 ($60,130.08) over the course of one year ( 3 ). One study by Murphy et al has shown low levels of concordance between resident and attending surgeons in CPT coding, possibly due to a lack of training ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of a template for clinical documentation can also serve as a means for improving resident instruction in coding. Other studies have shown that coding errors and omissions in patients resulted in cumulative loss of revenue of £46,750 ($60,130.08) over the course of one year ( 3 ). One study by Murphy et al has shown low levels of concordance between resident and attending surgeons in CPT coding, possibly due to a lack of training ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…One specific study reported an estimated revenue loss of over $80,000 in a 1-year period at a university outpatient clinic due to fewer level 4 visits when compared to Medicare normative data ( 2 ). These discrepancies result from incomplete clinical documentation which results in inadequate medical reimbursements ( 3 ). Previous studies have demonstrated that electronic medical record template use improves accuracy and completeness of both operative and clinical notes in orthopedic surgery, contributing to ease in interdisciplinary communication ( 4 - 6 ).…”
Section: Introductionmentioning
confidence: 99%